Pelatihan Ecoprint Memanfaatkan Daun dan Bunga Sebagai Bahan Penunjang Pembelajaran IPA di Sekolah Alam Kampung Wisata Isyo Hills Rhepang Muaif, Jayapura - Warikar, Evie L.; Ramandey, Euniche (Bakti Hayati: Jurnal Pengabdian Indonesia, 2024)
This community service activity with the theme of ecoprint training was carried out with the aims to increase the knowledge, skills, and understanding of students and teachers at Sekolah Alam "Isyo Hills" Kampung Rhepang Muaif, in utilizing wet leaves and flowers waste from the school environment into aninteresting and fun science learning tools.  The ecoprinting training activity was held on August 5, 2023 in Rephang Muaif Village, Nimbokrang, Jayapura-Papua, involving 16 participants representatives of early childhood and elementary school grades 1 to 5 from Sekolah Alam ‘’Isyo Hills”. The methods used in this ecoprint training activity are lectures/ counseling, discussions, direct practice of making ecoprints, and evaluation of activities. On the occasion of implementing the Community Service (PkM) program, the team provide a demonstration on how to manage wet leaves and flowers into valuable and useful products through ecoprint coloring techniques with the pounding or hammering method. The response in the form of participation and enthusiasm given by the participants in theseactivity was very good. With this activity, the teacher and students at Sekolah Alam “Isyo Hills” Kampung Rephang Muaif gained additional knowledge and increased abilities and skills in making ecoprinting. In addition, this activity also provides insight to students at Sekolah Alam to better protect the environment so as not to burn garbage. The other impact is an increase in the competence of elementary school teachers.